Analysis of Mobilization Factors, Personal Hygienic, Nutritional Status in Washing Perenium Healing in Women in Lamongan Health and Health Center - Siti Solikha; Siti Farida; Indasah Indasah (Journal for Quality in Public Health, 2020)
Perenium rupture is a tear that occurs in the perenium region during labor. Factors that influence the healing of perineal wounds include maternal nutritional needs that are sufficiently seen from the Body Mass Index (BMI), personal hygiene, mothers mobilizing. This study aims to determine the factors that influence the healing of perenium wounds in postpartum mothers at Turi Health Center and Lamongan Health Center in 2018. The research design used is quantitative research using a "cross sectional" approach. The sampling technique used is Simple Rendom Sampling with a sample of 116 respondents. Analysis technique with logistic regression test. The results of the analysis showed that there was a significant influence between the mobilization of p-value 0,000 <0,05, Personal Hygiene p-value 0,009 <0,05, and Nutritional Status p-value 0,009 <0,05 with healing of perennial wounds. And also found a significant simultaneous influence between personal hygiene mobilization, and nutritional status of perenium wound healing with a p-value of 0,000 <0,05 with the most dominant factor affecting wound healing is personal hygiene. Mother's personal hygiene helps reduce the source of infection and increases comfort in the mother. By preventing infection in perenium wounds, the wound can heal quickly